Institutionalizing violence: strategies of jihad in Egypt - Drevon, Jerome (Oxford University Press, 2022)
"This chapter presents the analytical framework of this book in the contentious politics research agenda. The book situates jihadi groups in a multilevel environment constituted by their political environment, social movement, the security services, the public, and a potential countermovement. This chapter argues that jihadi groups can successively radicalise in interaction with any of these actors. The first argument is that radicalisation forces them to institutionalise along one dimension. The second argument is that the succession of several phases of radicalisation and institutionalisation shapes their long-term trajectories and strategic choices"--